THE PHENOMENON OF MOVEMENT AT LINGUISTIC LEVELS AND THE TERMS EXPRESSING IT - Ergashev Sardor Kosimovich; Yuldasheva Nilufar Ergashevna (Modern American Journals, 2025)
This article examines the nature and interrelationships of phenomena widely used in modern linguistics, such as conversion, translation, transliteration, derivation, inversion, permutation, and transposition. Each term is distinguished by its unique semantic characteristics. The article discusses the theoretical foundations and practical applications of these processes. It presents significant scientific conclusions regarding the dynamic nature of linguistic phenomena and their role in contemporary explanatory dictionaries and translation systems.
Keywords: Transposition, conversion, translation, transliteration, derivation, inversion, permutation, transpositor, avalanche word.